Effects of epigallocatechin gallate incorporation in UHMWPE on biological behavior, oxidative degradation, mechanical and tribological performance for biomedical applications. (June 2021) - Kang, Xueqin; Zong, Xiaohui; Zhang, Peng; Zeng, Xiao; Liu, Yu; Yao, Chi; Wang, Tao; Feng, Peizhong; Yang, Chunmin
Abstract: Oxidation of ultrahigh-molecular-weight-polyethylene (UHMWPE) affects its physicochemical properties. Epigallocatechin gallate (EGCG) was added to improve UHMWPE antioxidant capacity. The extract of UHMWPE stabilized with EGCG (EGCG/UHMWPE) exhibits cytocompatibility and cell viability in vitro . The gamma irradiated UHMWPE and EGCG/UHMWPE present similar physicochemical properties. Mechanical and tribological properties of irradiated pure UHMWPE are deteriorated after accelerated aging, while these properties are maintained after adding EGCG. The wear mechanism of irradiated UHMWPE is mainly abrasive and fatigue wear after accelerated aging, while the addition of EGCG improves the fatigue resistance and reduces the number of flakes and ruptures of irradiated UHMWPE. Highlights: ECCG/UHMWPE extract exhibits cytocompatibility and cell viability in vitro. EGCG has little effect on physicochemical behavior of gamma irradiated UHMWPE. EGCG addition reduces the deterioration of irradiated UHMWPE tribological behaviors. Friction and wear model of EGCG/UHMWPE after irradiation and aging was established.